2022
DOI: 10.2147/ijwh.s382836
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Exosome Concentration and Exosomal microRNA (miR-155 and miR-222) Expression in Pregnant Women with Gestational Hypertension and Preeclampsia

Abstract: Introduction Hypertensive disorders of pregnancy are characterized by widespread maternal endothelial dysfunction. Elevated secretion of exosomes has been associated with endothelial dysfunction. Exosomes play a role in cell–cell communication by transferring microRNAs. These microRNAs are associated with the pathogenesis of hypertensive disorders of pregnancy through the regulation of endothelial function. This study characterizes exosomes and determines exosomal miR-155 and miR-222 expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The results demonstrated that an increase in circulating miR-31 was associated with early onset preeclampsia; meanwhile, an increase in circulating miR-21 was related to late-onset preeclampsia [119]. Decreased levels of circulating miR-126 were associated with early onset preeclampsia compared to gestation-matched controls [128]. Kolkova et al verified the expression of miRNAs isolated from the venous blood of women with pregnancy complicated by preeclampsia.…”
Section: Mirnas and Onset Of Preeclampsiamentioning
confidence: 99%
“…The results demonstrated that an increase in circulating miR-31 was associated with early onset preeclampsia; meanwhile, an increase in circulating miR-21 was related to late-onset preeclampsia [119]. Decreased levels of circulating miR-126 were associated with early onset preeclampsia compared to gestation-matched controls [128]. Kolkova et al verified the expression of miRNAs isolated from the venous blood of women with pregnancy complicated by preeclampsia.…”
Section: Mirnas and Onset Of Preeclampsiamentioning
confidence: 99%
“…Recently, specific proteins, miRNAs associated with PE cases have been found within exosomes isolated from the maternal sera 55 , 56 . Evaluation of the profile of these circulating exosomes derived from PE patients could be beneficial as they are present since early gestation with their concentration and cargo altering under a pathological state.…”
Section: Serum Exosomes In Healthy Pregnancy and Pre-eclampsiamentioning
confidence: 99%
“…Recently, numerous investigations have been published describing the putative roles of various small RNAs in PE, but the overlap among these predicted targets is typically small (33,(53)(54)(55)(56)(57)(58)(59). Apart from technical differences, a major concern with these investigations is that the included patient groups in these studies were not generally uniform due to the inherent heterogeneity of the disease.…”
Section: Introductionmentioning
confidence: 99%